Photovoltaic and Micro-Hydroelectric Proposed Plant for Stand Alone Electric Generation in a Sixty-Floor Skyscraper (P60). Issue 29 (2016) - Bylykbashi, K.; Capata, R.; Cirillo, R.
Abstract: The aim of this paper is the feasibility study of a micro-hydroelectric (Pelton turbine with a rated power lower than 50 kW) and a Photovoltaic plant integrated in a sixty floor skyscraper. In this proposal, the hydraulic plant is located in the foundation and it is designed to use the greywater from each apartment; the photovoltaic system is on the top of the building, to take advantage of the height and the wind. A multi-tank configuration has been analyzed, its periodical emptying, fixes and regulate the turbine working cycles, guaranteeing a steady power generation; at the bottom of this turbine, a high efficient ultra-filtration plant has been designed. The purified water is now ready to be pumped back to the users and used again. On the roof, there are 28 solar strings, each one of 25 serial panels made, facing south and installed at a tilt angle of 35°. The total power is 165 kWp .